Study of Chemical Composition and Evaluation of Anti-hypertensive Effect of A Fixed Oil Extracted from Linum usitatissimum grains - Halima, Oulad Ali; Mebarka, Belboukhari; Nasser, Belboukhari; Khaled, Sekkoum; Kawther, Al Sid Chikh (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2024)
Globally grown flax seed is regarded as an oilseed with numerous medicinal and health are the outcomes of the physico-chemical analyses: pH value: 0.476; saponification index: 168.3; KOH/g: 28.05; peroxide index: 174; density: 0.951; refractive index: 1.482 at 18.1°C and 1.485 at 18.2°C; peroxide index: 1.70 at 0.96, 1.70 mg/100; all are related to the peroxide index. In this study we tried to test the ” anti-hypertension “ activity of this oil by simulating a blood cycle in the laboratory which allowed us to determine the variation in blood pressure as a function of the volume of oil injected into the blood cycle from 17.4 to 14.10. benefits such as: lowering blood pressure, blood sugar, decreasing the risk of neurological and obesity-related illnesses. The objective of this study is to extract the linseed oil and to characterize it chemically and physically; by pressing the seeds into two different temperatures : 67°C and 90°Coil yields ; 24% and 29% were obtained from linseed. The followings